Cutaneous Manifestations Of Hepatitis B And C Virus Infections : A Study Of 100 Cases - Kochhar Atul Mohan; Reddy Belum Siva Nagi (Wolters Kluwer Medknow Publications, 2003)
Infection with hepatitis viruses, especially B and C, is a major public health problem in many countries. One hundred consecutive patients with these infections were studied for cutaneous abnormalities. Females were more commonly affected. Recurrent/chronic vascular changes (92%) , urticaria (72%), leucocytoclastic vasculitis (36%), erythema nodosum (28%), Gianotti-Crosti syndrome (12%), lichen planus (8%), pyoderma gangrenosum (2 patients) and dermatomyositis like syndrome (1 patient) were the prominent cutaneous abnormalities noted in patients with hepatitis B. Likewise, the prominent skin abnormalities notes in hepatitis â€" C Patients were vascular changes (82.2%), chronic urticaria (60.0%), xerosis of skin (56.6%), leucocytoclastic vasculitis (40%), erythema multiforme (23.3%), Sjogrenâ€s syndrome (13.2%), recurrent erythema nodosum (19.8%) and Behcetâ€s syndrome in a single case. Extensive subcutaneous fat atrophy of the face in one case and diffuse hyperpigmentation in 5 cases were the two interesting features noted in out patients, which have not been reported earlier. The pertinent literature is briefly reviewed in the light of above findings.